THE LEVEL OF SATISFACTION AND OBSTACLES TO THE USE OF ELECTRONIC LEARNING IN THE FACULTY OF MEDICINE, UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Indra, Muhammad Abdul Piki; Isnayanti, Desi (Medicina Biomedica Journal, 2024)
The level of satisfaction and obstacles to the use of e-learning can be measured through a questionnaire. The level of satisfaction can be influenced by the student's perception factor which plays an important role in the level of satisfaction of using e-learning in lectures. The level of satisfaction is all conditions and influences from within students on the use of e-learning. The higher the level of satisfaction with the use of e-learning, the higher the interest of students in using e-learning so that they will appear satisfied. Objectives: This study aims to determine the level of satisfaction and obstacles to the use of e-learning at UMSU Medical Faculty. Methods: This research is a quantitative descriptive study with a cross sectional design. The research sample consisted of 68 students of FK UMSU class 2019, 2020 and 2021 which were taken using the consecutive sampling method. This study was tested with a satisfaction level questionnaire that has been validated with SPSS, the value of Rcount Rtable. Results: Overall, the results showed that they were satisfied with students' perceptions of e-learning with a total score of 77.7%. The mean value of the satisfaction level component shows good results on student perceptions of e-learning. The highest obstacles encountered are device errors and server down. Conclusion: Students' perceptions of the use of e-learning are categorized as satisfied and problems are found, especially device errors and serverdowns.Keyword : e-learning, constraints, level of satisfaction